Method for synthesizing conjugated microporous polymer through metal-free catalysis and application
The synthesis of conjugated microporous polymers via a metal-free Scholl reaction solves the problems of metal residue and high cost in traditional methods, achieving efficient and environmentally friendly CMP preparation, applicable to fields such as iodine vapor adsorption and catalyst supports.
Patent Information
- Application Number
- CN202510995864.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional methods for synthesizing conjugated microporous polymers (CMPs) rely on metal catalysts, which result in metal residues, high costs, significant environmental pollution risks, high energy consumption, and complex synthesis steps.
Using triphenylamine as a monomer and N-iodosuccinimide and trifluoromethanesulfonic acid as catalysts, a metal-free Scholl reaction was carried out to synthesize conjugated microporous polymers (CMPs), thus avoiding the use of metal catalysts.
A conjugated microporous polymer with no metal residue was successfully prepared. It has an ultra-high specific surface area and excellent adsorption performance, and is suitable for iodine vapor adsorption, catalyst support and gas separation. It is environmentally friendly and low cost.
Smart Images

Figure CN120988254A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conjugated microporous polymer preparation, specifically relating to a method and application of metal-free catalytic synthesis of conjugated microporous polymers (CMPs). Background Technology
[0002] Conjugated microporous polymers (CMPs) are a new class of porous materials with unique structures and excellent properties. Their highly conjugated framework structure combined with abundant micropores gives them extremely broad application prospects in many cutting-edge fields such as gas adsorption and separation, heterogeneous catalysis, chemical sensing, and energy storage. For example, in gas adsorption, CMPs can efficiently adsorb gas molecules such as carbon dioxide and hydrogen, providing potential technical support for addressing global climate change and the energy crisis; in heterogeneous catalysis, they can serve as high-performance catalyst supports, significantly improving the selectivity and efficiency of catalytic reactions; in sensing, CMPs can rapidly respond to and detect specific chemical substances, providing sensitive detection methods for environmental monitoring and biomedical diagnostics; and in energy storage, they can be used to construct high-performance battery electrode materials or supercapacitors, contributing to the development of efficient energy storage and conversion technologies.
[0003] However, most traditional CMP synthesis methods rely on metal catalysts, such as the Suzuki coupling reaction (publication number CN119930996A), the Sonogashira coupling reaction (publication number CN 119331227 A), and the Yamamoto coupling reaction (Macromolecules 2009, 42 (13), 4426-4429). While these methods have played an important role in the synthesis of CMPs, they also have many significant drawbacks. First, the use of metal catalysts often leads to metal residues, which not only contaminates the final product and affects its performance in applications requiring high purity, but also poses a potential environmental pollution risk. Second, metal catalysts themselves are expensive, and the reaction conditions must be strictly controlled to ensure their activity, further increasing the synthesis cost of CMPs. In addition, these traditional synthesis methods typically require large amounts of organic solvents and complex reaction steps, resulting in high energy consumption and the generation of large amounts of waste, placing a significant burden on the environment and contradicting the requirements of modern society for green chemistry and sustainable development. Summary of the Invention
[0004] The technical problem to be solved by this invention is to provide a metal-free catalytic synthesis method for conjugated microporous polymers (CMPs) based on the iodine-catalyzed Scholl reaction, addressing the shortcomings of existing technologies. This invention uses triphenylamine (TPA) as a monomer, introduces N-iodosuccinimide (NIS) as an iodizing agent, and combines this with the synergistic catalytic effect of trifluoromethanesulfonic acid (TfOH) to successfully synthesize conjugated microporous polymers (TPA-CMPs) without the need for a metal catalyst.
[0005] This invention provides a metal-free catalytic synthesis method for conjugated microporous polymers (CMPs) based on iodine-catalyzed Scholl reaction. Triphenylamine and N-iodosuccinimide are dissolved in a low-polarity solvent; trifluoromethanesulfonic acid (TfOH) is added to the above reaction system as an oxidative coupling catalyst, and the mixture is stirred to carry out a Scholl coupling polymerization reaction to obtain metal-free conjugated microporous polymers TPA-CMPs.
[0006] According to the above scheme, the molar ratio of triphenylamine to N-iodosuccinimide is 1:2~4.
[0007] According to the above scheme, the molar ratio of triphenylamine to trifluoromethanesulfonic acid is 1:2.26~13.6.
[0008] According to the above scheme, the low-polarity solvent is 1,2-dichloroethane, chlorobenzene, or o-dichlorobenzene.
[0009] According to the above scheme, the stirring time is 2-6 hours.
[0010] According to the above plan, the temperature after stirring should be 0~80℃, and maintained for 12~48 hours.
[0011] According to the above scheme, the product obtained by reaction separation was washed sequentially with N,N-dimethylformamide, ethanol and tetrahydrofuran, and rinsed with deionized water until neutral. After low-temperature freeze drying, conjugated microporous polymer TPA-CMPs powder was obtained.
[0012] According to the above scheme, the low-temperature freeze-drying conditions are -50±5°C for 2~10 hours.
[0013] According to the above scheme, the specific surface area of the metal-free catalytic synthesis of conjugated microporous polymers (CMPs) is 759-1334 m² / g, and the pore size is 0.1-11 nm.
[0014] The present invention provides the application of the metal-free catalytically synthesized conjugated microporous polymers (CMPs) synthesized by the above method as iodine adsorption materials, catalyst supports, gas separation materials or environmental remediation materials.
[0015] This invention uses triphenylamine as the starting substrate and N-iodosuccinimide (NIS) as the iodination catalyst to achieve selective iodination at specific positions without the need for metal complexes, generating a tri(4-iodophenyl)amine intermediate. Subsequently, under the synergistic catalysis of trifluoromethanesulfonic acid (TfOH), the tri(4-iodophenyl)amine intermediate undergoes oxidative deiodination, driving Scholl coupling polymerization to ultimately achieve the efficient preparation of CMPs. This invention solves the problems of high pollution, high cost, and catalyst residue in traditional metal-catalyzed CMP synthesis processes, providing a new route for green chemical synthesis and significantly improving the renewability and adsorption performance of the materials.
[0016] The beneficial effects of this invention are as follows: This invention provides a novel, metal-free method for synthesizing CMPs based on the iodine-catalyzed activation of triphenylamine to form an iodinated triphenylamine intermediate, followed by oxidative deiodination under the promotion of trifluoromethanesulfonic acid (TfOH). By leveraging the synergistic effect of NIS and TfOH to achieve directional iodization and efficient coupling polymerization of triphenylamine, a TPA-CMP material with an ultra-high specific surface area (1334.6 m² / g) and excellent adsorption performance (static adsorption capacity for iodine vapor reaching 5.7 g / g) was successfully prepared. This method requires no precious metal catalyst, is highly efficient, environmentally friendly, and features a mild and controllable process.
[0017] The TPA-CMP material of this invention has an ultra-high specific surface area and excellent adsorption performance. It is not only suitable for iodine vapor adsorption, but can also be applied to multiple fields such as catalyst support, gas separation and environmental remediation, and has good economic benefits and industrial application prospects. Attached Figure Description
[0018] Figure 1 The figures show the FT-IR spectra of the TPA-CMP materials prepared in Examples 1-3. In the figures, 0.5 mL represents Example 2 (TPA-CMP-0.5), 1.5 mL represents Example 1 (TPA-CMP-1.5), and 3 mL represents Example 3 (TPA-CMP-3).
[0019] Figure 2 The figures show (a) nitrogen adsorption isotherms and (b) pore size distributions of the TPA-CMP materials prepared in Examples 1-3 at 77 K. In the figures, 0.5 mL represents Example 2 (TPA-CMP-0.5), 1.5 mL represents Example 1 (TPA-CMP-1.5), and 3 mL represents Example 3 (TPA-CMP-3).
[0020] Figure 3The X-ray diffraction patterns of TPA-CMPs prepared under different TfOH contents in Examples 1-3 are shown in the figure. In the figure, 0.5 mL is Example 2 (TPA-CMP-0.5), 1.5 mL is Example 1 (TPA-CMP-1.5), and 3 mL is Example 3 (TPA-CMP-3).
[0021] Figure 4 The figures show the adsorption isotherms of iodine on TPA-CMPs obtained in Examples 1-3 at 353 K. In the figures, 0.5 mL is Example 2 (TPA-CMP-0.5), 1.5 mL is Example 1 (TPA-CMP-1.5), and 3 mL is Example 3 (TPA-CMP-3).
[0022] Figure 5 (a) and (b) pore size distribution of nitrogen adsorption isotherms of TPA-CMPs obtained in Examples 4-6 at different TPA:NIS ratios; (c) FT-IR spectra and (d) XRD patterns of TPA-CMPs at different TPA:NIS ratios. In the figures: TPA:NIS=1:2 – Example 4 (TPA-CMP-1:2), TPA:NIS=1:4 – Example 5 (TPA-CMP-1:4), TPA:NIS=1:4 – Example 6 (TPA-CMP-1:3).
[0023] Figure 6 This is a schematic diagram of the metal-free catalytic synthesis of conjugated microporous polymers (CMPs) based on the iodine-catalyzed Scholl reaction using 1,2-dichloroethane (DCE) as a solvent. Detailed Implementation
[0024] The present invention will be further described in detail below with reference to specific embodiments.
[0025] Example 1 Conjugated microporous polymers (TPA-CMPs) were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), N-iodosuccinimide (NIS) (1.6873 g, 7.5 mmol), and anhydrous 1,2-dichloroethane (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (1.5 mL) was added dropwise at room temperature (25 °C). The reaction mixture was stirred at room temperature for 3 hours, then heated at 80 °C for 48 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. A schematic diagram of the metal-free catalytic synthesis of conjugated microporous polymers (CMPs) based on an iodine-catalyzed Scholl reaction using 1,2-dichloroethane (DCE) as the solvent is shown below. Figure 6 As shown. The solid product was washed sequentially with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly rinsed with water until the pH reached neutral. The purified product was freeze-dried at -50±5°C for 8 hours to obtain a brown powder TPA-CMP (yield 96%), denoted as TPA-CMP-1.5.
[0026] Fourier transform infrared spectroscopy display ( Figure 1 ), at 815 cm -1 An absorption peak appeared at the point where the disubstituted benzene ring appeared, indicating that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring through oxidative coupling. The specific surface area reached 1334 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 2 a). Pore size analysis further showed that the pore size ranged from 8 to 11 nm ( Figure 2 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-1.5 sample was amorphous. Figure 3 ).
[0027] Adsorption effect of TPA-CMP-1.5 on radioactive iodine: Accurately weighed elemental iodine (1.0000 g, excess) was placed at the bottom of a PTFE-lined autoclave. 0.0500 g of TPA-CMP-1.5 sample was loaded into a pre-weighed glass weighing bottle (initial mass recorded as m1) and then placed vertically in the autoclave liner. After sealing, the reaction system underwent static adsorption experiments in an 80°C constant temperature oven. At specified time intervals (2 h, 4 h, 6 h, 8 h, 10 h, 24 h, 29 h, 34 h, and 48 h), the weighing bottle was removed, cooled to room temperature in a desiccator, and its total mass (m2) was measured when the sample mass remained constant. The iodine adsorption capacity (w) was calculated using the formula: w = (m2−m1) / m, expressed in gg⁻¹. The adsorption capacity of the TPA-CMP-1.5 sample was 5.7 g / g ( Figure 4 ).
[0028] Example 2 Conjugated microporous polymers TPA-CMPs were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), NIS (1.6873 g, 7.5 mmol), and chlorobenzene (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (0.5 mL) was added dropwise at 25°C. The reaction mixture was stirred at room temperature for 4 hours, followed by heating at 80°C for 36 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. The solid product was washed successively with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly washed with water until the pH reached neutral. The purified product was freeze-dried at -50 ± 5°C for 2 hours to obtain a brown powder, TPA-CMP (62% yield), denoted as TPA-CMP-0.5.
[0029] Fourier transform infrared spectroscopy display ( Figure 1 ), at 815 cm -1 An absorption peak appeared at the point where the disubstituted benzene ring appeared, indicating that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring through oxidative coupling. The specific surface area reached 1040 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 2 a). Pore size analysis further showed that the pore size ranged from 0.1 to 9 nm ( Figure 2 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-0.5 sample was amorphous. Figure 3 ).
[0030] Adsorption effect of TPA-CMP-0.5 on radioactive iodine: Accurately weighed elemental iodine (1.0000 g, excess) was placed at the bottom of a PTFE-lined autoclave. 0.0500 g of TPA-CMP-0.5 sample was loaded into a pre-weighed glass weighing bottle (initial mass recorded as m1) and then placed vertically in the autoclave liner. After sealing, the reaction system underwent a static adsorption experiment in an 80°C oven. At specified time intervals (2 h, 4 h, 6 h, 8 h, 10 h, 24 h, 29 h, 34 h, and 48 h), the weighing bottle was removed, cooled to room temperature in a desiccator, and its total mass (m2) was measured when the sample mass remained constant. The iodine adsorption capacity (w) was calculated using the formula: w = (m2−m1) / m, expressed in gg⁻¹. The adsorption capacity of the TPA-CMP-0.5 sample was 4.3 g / g ( Figure 4 ).
[0031] Example 3 Conjugated microporous polymers TPA-CMPs were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), NIS (1.6873 g, 7.5 mmol), and chlorobenzene (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (3.0 mL) was added dropwise at 25°C. The reaction mixture was stirred at room temperature for 2.5 hours, followed by heating at 80°C for 12 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. The solid product was washed successively with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly washed with water until the pH reached neutral. The purified product was freeze-dried at -50 ± 5°C for 6 hours to obtain a brown powder, TPA-CMP (yield 94%), designated TPA-CMP-3.0.
[0032] Fourier transform infrared spectroscopy display ( Figure 1 ), at 815 cm -1 An absorption peak appeared at the point where the disubstituted benzene ring appeared, indicating that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring via oxidative coupling. The specific surface area reached 1272 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 2 a). Pore size analysis further indicates that the pore size ranges from 1 to 5 nm ( Figure 2 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-3.0 sample was amorphous. Figure 3 ).
[0033] Adsorption effect of TPA-CMP-3.0 on radioactive iodine: Accurately weighed elemental iodine (1.0000 g, excess) was placed at the bottom of a PTFE-lined autoclave. 0.0500 g of TPA-CMP-3.0 sample was loaded into a pre-weighed glass weighing bottle (initial mass recorded as m1) and then placed vertically in the autoclave liner. After sealing, the reaction system underwent a static adsorption experiment in an 80°C oven. At specified time intervals (2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 24 hours, 29 hours, 34 hours, and 48 hours), the weighing bottle was removed, cooled to room temperature in a desiccator, and its total mass (m2) was measured when the sample mass remained constant. The iodine adsorption capacity (w) was calculated using the formula: w = (m2−m1) / m, expressed in gg⁻¹. The adsorption capacity of the TPA-CMP-3.0 sample was 5.5 g / g ( Figure 4 ).
[0034] Example 4 Conjugated microporous polymers TPA-CMPs were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), NIS (1.1249 g, 5.0 mmol), and anhydrous 1,2-dichloroethane (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (1.5 mL) was added dropwise at 25°C. The reaction mixture was stirred at room temperature for 3.5 hours, followed by heating at 40°C for 36 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. The solid product was washed successively with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly rinsed with water until the pH reached neutral. The purified product was freeze-dried at -50±5°C for 8 hours to obtain a brown powder TPA-CMP (yield 78%), denoted as TPA-CMP-1:2.
[0035] Fourier transform infrared spectroscopy display ( Figure 5 c), at 815 cm -1 An absorption peak appeared at the point where the disubstituted benzene ring appeared, indicating that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring through oxidative coupling. The specific surface area reached 759 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 5 a). Pore size analysis further showed that the pore size ranged from 0.3 to 8 nm ( Figure 5 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-1:2 sample was amorphous. Figure 5 d).
[0036] Example 5 Conjugated microporous polymers TPA-CMPs were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), NIS (2.2498 g, 10 mmol), and anhydrous 1,2-dichloroethane (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (1.5 mL) was added dropwise at 0°C. The reaction mixture was stirred at room temperature for 5 hours, and then reacted at 0°C for 48 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. The solid product was washed successively with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly washed with water until the pH reached neutral. The purified product was freeze-dried at -50±5°C for 8 hours to obtain a brown powder TPA-CMP (yield 98%), denoted as TPA-CMP-1:4.
[0037] Fourier transform infrared spectroscopy display ( Figure 5 c), at 815 cm -1 The presence of an absorption peak for the disubstituted benzene ring indicates that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring via oxidative coupling. The specific surface area reached 1192 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 5 a). Pore size analysis further showed that the pore size ranged from 0.4 to 7 nm ( Figure 5 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-1:4 sample was amorphous. Figure 5 d).
[0038] Example 6 Conjugated microporous polymers TPA-CMPs were synthesized via an iodine-catalyzed Scholl reaction using triphenylamine as the monomer and NIS and TfOH as dual catalysts. The detailed synthetic steps are as follows: Triphenylamine (0.6133 g, 2.5 mmol), NIS (1.6873 g, 7.5 mmol), and o-dichlorobenzene (5 mL) were added to a 25 mL round-bottom flask equipped with a magnetic stirrer. Then, TfOH (1.5 mL) was added dropwise at 20°C. The reaction mixture was stirred at room temperature for 4.3 hours, and then reacted at 60°C for 48 hours. After the reaction was complete, the system was cooled to room temperature, and the precipitate was separated by vacuum filtration. The solid product was washed successively with N,N-dimethylformamide, ethanol, and tetrahydrofuran, and then thoroughly washed with water until the pH reached neutral. The purified product was freeze-dried at -50±5°C for 8 hours to obtain a brown powder TPA-CMP (yield 93%), denoted as TPA-CMP-1:3.
[0039] Fourier transform infrared spectroscopy display ( Figure 5 c), at 815 cm -1 An absorption peak appeared at the point where the disubstituted benzene ring appeared, indicating that the triphenylamine with a monosubstituted benzene ring was successfully converted into the TPA-CMP polymer with a disubstituted benzene ring via oxidative coupling. The specific surface area reached 1021 cm² / g, which can be calculated from the nitrogen adsorption-desorption isotherm. Figure 5 a). Pore size analysis further showed that the pore size ranged from 7 to 10 nm ( Figure 5 b). X-ray diffraction (XRD) analysis confirmed that the synthesized TPA-CMP-1:3 sample was amorphous. Figure 5 d).
[0040] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A method for metal-free catalytic synthesis of conjugated microporous polymers based on iodine catalyzed Scholl reaction, characterized in that: Triphenylamine and N-iodosuccinimide are dissolved in a small polar solvent; trifluoromethanesulfonic acid is added to the above reaction system as an oxidative coupling catalyst, stirring, Scholl coupling polymerization reaction is carried out, and metal-free conjugated microporous polymers TPA-CMPs are obtained.
2. The method of claim 1, wherein: The molar ratio of triphenylamine to N-iodosuccinimide is 1:2-4.
3. The method of claim 1, wherein: The molar ratio of triphenylamine to trifluoromethanesulfonic acid is 1:2.26-13.
6.
4. The method of claim 1, wherein: The small polar solvent is 1,2-dichloroethane, chlorobenzene or o-dichlorobenzene.
5. The method of claim 1, wherein: The stirring time is 2-6 h.
6. The method of claim 1, wherein: The temperature is controlled to be 0-80℃ after stirring, and maintained for 12-48 h.
7. The method of claim 1, wherein: The obtained product after reaction separation is successively washed with N,N-dimethylformamide, ethanol and tetrahydrofuran, and washed with deionized water until neutral, and low-temperature freeze-dried to obtain conjugated microporous polymer TPA-CMPs powder.
8. The method of claim 7, wherein: The low-temperature freeze-drying condition is 2-10 h at-50±5℃.
9. The method of claim 1, wherein: The specific surface area of the metal-free catalytic synthesis conjugated microporous polymer is 759-1334 m² / g, and the pore size is 0.1-11 nm.
10. The application of the metal-free catalytic synthesis conjugated microporous polymer synthesized by the method of any one of claims 1-9 as an iodine adsorption material, a catalytic carrier, a gas separation material or an environmental remediation material.
Citation Information
Patent Citations
Triphenylamine-based conjugated microporous polymer as well as preparation method and application thereof
CN119331227A
Novel aza conjugated microporous polymer wave-absorbing material and preparation method thereof
CN119930996A